APLIKASI SISTEM PAKAR DIAGNOSA PENYAKIT AYAM STUDI KASUS: PADA CV. INTAN JAYA ABADI SUKABUMI - Yusti Farlina; Jamal Maulana Hudin (Swabumi, 2016)
Expert systems are computer programs that mimic the thought processes and expert knowledge to solve aparticular problem. Implementation of expert systems are widely used for commercial purposes becausethe expert system is seen as a way of storing the knowledge of experts in specific fields into a computerprogram so as to give a decision and to reason intelligently. This study will discuss Disease DiagnosisExpert System for Chickens. There is also the method used is a rule-based method to search back andsearch forward, with a design that is easy and in accordance with existing rules. Then the programcreated is expected to represent an expert in diagnosing diseases of chicken. Expert systems are createdare used as decision support and used as a tool for one to know the solution of problems in the Chicken.Rule-based representation in expert systems provide benefits in several aspects, namely the ease ofmodifying, both additions, changes, or eliminate.